Queer multicultural social justice education : curriculum (and identity) development through performance - Knaier, Michelle Lynn (Research for social justice., 2021)
"In Queer Multicultural Social Justice Education: Curriculum (and Identity) Development Through Performance, I take a pragmatic approach sharing my intimate journey, my stories, and myself with you-the reader-as I actively perform and model the development of queer explorations (i.e., lessons) and curriculum. I begin this journey with three accessible histories of multicultural education, queer perspectives, and autoethnography, respectively. These easy-to-navigate stories provide you with important background knowledge, highlighting the evolution of, commonalities between, and need for each discipline, along with their connection to identity and identity awareness as a form of social justice practice and advancement. Next, I share and perform the nine explorations developed for this project, collectively titled Queer Explorations of Identity Awareness. Modeling for you in practical terms how to queer curriculum and its development, I openly examine my raw performances, discuss my personal and analytical reflections, and embrace my own personal experiences and revelations that occurred throughout this project. Finally, I close with a creative, reflective, and story-like analysis of the process that includes a call to action from you to share your stories as a way of knowing yourself-and others-as a form of social justice education and advancement. This book is intended for all formal and informal educators interested in performing and developing queer multicultural social justice curriculum and practices. Inspired by Ayers (2006), I invite you on this "voyage" with "hope and urgency" (p. 83). It is time we share our stories as a form of curriculum, activism, and coming together"--